PROSPEK KOMODITAS MINYAK KELAPA SAWIT (CPO) DALAM PENGEMBANGAN BIODIESEL SEBAGAI ALTERNATIF BAHAN BAKAR DI INDONESIA - Ermi Tety; Sakti Hutabarat; Fajar Manggala Putra (Program Studi Pendidikan Ekonomi Universitas Riau, 2013)
Agricultural sector than as producers of renewable energy as well as a potentialuser. The calculation of the balance between production and use of renewableenergy in the agricultural sector needs to be studied simultaneously, in line withtechnological developments in energy and agriculture. This evaluation will be usefulto assess the efficiency of the agribusiness in Indonesia in terms of increasingnational agricultural productivity and environmental conservation through renewableenergy. Agricultural products that have the potential to be used as an oil substitute isbiodiesel. Apart from a fairly competitive selling point, biodiesel is also consideredenvironmentally friendly and a renewable energy because it uses raw materials fromagricultural products. During the last five-year period in which oil prices soar, theprice of biodiesel is lower to the substitution of petroleum products and the potentialand feasible to produce. The results of the NPV (Rp 44.7 billion) and IRR (38.94percent) in this study demonstrate the feasibility of biodiesel production.Keyword : feasibility study, biodiesel, renewable energy, cpo (crude palm oil).